Europe's other arms production problem: "New Defense" - Lucie Béraud-Sudreau (EconPol Forum, 2024)
"New Defense," akin to "NewSpace," challenges the traditional defense industry with innovative, agile, software-first companies. Lack of European equivalent to US tech giants raises concerns about strategic credibility. European technology sector's military assistance to Ukraine remains limited compared to the US. Europe's New Defense sector is critical for future military capabilities and strategic credibility.
Keywords: 330